A comparative study of intrathecal bupivacaine and levobupivacaine for patients undergoing caesarean section - Kaur, Kiranpreet; Johar, Sanjay; Kumar, Anil; Jain, Mamta; Kumar, Prashant; Singh, Anish (International Journal of Advances in Medicine, 2019)
Background: The present study was conducted to compare the effects of 0.5% isobaric levobupivacaine and 0.5% hyperbaric bupivacaine in pregnant females undergoing caesarean section. Methods: Study was conducted on 100 pregnant females undergoing caesarean section. They were randomly divided into two groups B and L receiving 2 ml of 0.5% hyperbaric bupivacaine and 0.5% levobupivacaine respectively. Two groups were compared with regard to sensory block, motor block, haemodynamic stability and complications if any. Results: Time to achieve sensory blockade till T6 dermatome was prolonged in group B (162.52±80.55 sec) as compared to group L (139.40±49.79 seconds) (p value= 0.087). Prolonged duration of motor blockade was observed in group B (160.76±6.56 minutes) as compared to group L (131.48±14.42 minutes) (p<0.001). Less haemodynamic stability was seen in patients of group B with more incidence of hypotension and bradycardia.as compared to group L. Conclusions: Levobupivacaine is nearly equally effective to bupivacaine to produce sensory and motor blockade with comparable onset time and better haemodynamic stability with lesser side effects.